"Legal Exposure": lifting the corporate veil in deciding matrimonial property (harta sepencarian) - Ibrahim, Norliah; Abd Ghadas, Zuhairah Ariff (Sweet & Maxwell Asia, 2009)
The doctrine of lifting the corporate veil is a legal principle applied by the court to set aside the separate legal entity of a company in order to discover the truth behind the veil of incorporation. Despite its frequent use, the doctrine of lifting the corporate veil is only applied by the court under justified circumstances, for example when physical attributes of the company are required, in cases involving fraud or when the company is used as a sham, alter ego or agent of the owner/members for certain purposes. In today's business world, there are many methods which are adopted by businessmen to hide their personal interest in the business's assets/property. One of the ways is by transferring personal property to the companies or by using the company to buy assets which are meant for the owner/members. Under the doctrine of separate legal entity, a company can hold land/property under its own name and the members/owners have no interest in the company's property/assets. This doctrine could create problems to divorced couples in determining the matrimonial property, particularly if one of the parties conceals his/her personal interest behind the corporate entity which he/she owns. This paper intends to discuss the possibilities of applying the doctrine of lifting of the corporate veil in determining matrimonial property in cases which involve property/assets under the company's name. Research methodologies which are adopted for this paper are statutory and doctrinal analysis.